Preparedness and response to the international poliovirus and diphtheria reintroduction alert: public health interventions and strategy review in the Veneto Region, Italy - Milani, Marco; Nicoletti, Michele; Tonon, Michele; Gentili, Davide; Panaite, Stefan-Alexandru; Da Re, Filippo; Basso, Andrea; Pagin, Gloria; Zampini, Marco; Ballarin, Debora; Zanella, Francesca; Groppi, Vanessa; et al. (Frontiers in Public Health, 2025)
BackgroundDiphtheria and polio continue to pose significant public health challenges globally, making sustained high vaccination coverage crucial. This study examines the strategies adopted in the Veneto Region to enhance vaccination rates for diphtheria and polio among priority target groups and improve poliovirus surveillance, following the WHO alert about the potential reintroduction and circulation of the two pathogens.AimThe main objective of this study is to assess the effectiveness of supplementary vaccination strategies implemented in the Veneto Region in response to international poliomyelitis and diphtheria alerts. Additionally, it aims to identify municipalities at higher risk of poliovirus AFP based on georeferenced vaccination coverage, enhancing environmental surveillance strategies. Ultimately, the study evaluates regional preparedness and response efforts, offering insights to mitigate the risk of reintroducing these diseases and providing a framework adaptable to similar contexts.MethodsThe Regional Directorate of Prevention, Food Safety, Veterinary Public Health analysed regional vaccination coverage and provided Local Health Authorities (LHAs) with a georeferenced representation of vaccination coverage across municipalities. Directives on targeted vaccination strategies were issued to address identified gaps and improve readiness. Ten months later, the Regional Directorate assessed the approaches implemented by LHAs to improve vaccine uptake and evaluated the resulting vaccination coverage. Based on this georeferenced analysis, the effectiveness of current environmental poliovirus surveillance was reviewed, and recommendations for optimising surveillance efforts were proposed.ResultsFollowing the implementation of the vaccination strategies recommended by the Regional Directorate, vaccination rates improved across all LHAs, especially among children aged 0–2 years who had not received any vaccine doses. The georeferenced analysis of vaccination coverage revealed critical gaps in environmental poliovirus surveillance and underscored the need for targeted interventions to reach unvaccinated populations.ConclusionThis study demonstrates that centralised governance, combined with georeferenced vaccination data, environmental poliovirus surveillance, and clinical AFP surveillance, enhances the ability to identify coverage gaps and respond to infectious disease threats. While improvements in vaccination rates were achieved, the findings underscore the need for targeted, community-specific interventions and continuous monitoring to address disparities. Strengthening data integration and adopting innovative surveillance methods will be crucial to sustaining high vaccination coverage and ensuring public health security.